Investigation on Influence Factors of the C-REIT Market: Applying the Fama-French Three-Factor Model - Huang, Mingda (Transactions on Economics, Business and Management Research, 2024)
This research paper has applied the Fama-French Three-Factor Model to the China Real Estate Investment Trust (C-REIT) market over a two-year period from June 2022 to June 2024. The innovation is recognized as the C-REIT market was established in 2021 with the first 9 REITs issued and few researches were conducted on the C-REITs. The study obtained data from the Wind database in the after-COVID period and concluded that the model fits well for the behavior of the Chinese REIT market. The market premium factor is found to be positive, while the size factor (SMB) is negatively significant, and the value premium (HML) is positively significant. This suggests that REITs with smaller market capitalization and those with a higher book-to-market ratio are more likely to contribute to the portfolio’s excess returns. The intercept in the regression is statistically significant and that implies that there may be additional factors that are not captured by the current model. As such, the paper advocates for further research into multi-factor models to explore potential factors.